Antinociceptive and anti-inflammatory effects of the ethanol extract of Alpinia conchigera rhizomes in various animal models. - Sulaiman, Mohd Roslan; Zakaria, Zainul Amiruddin; Tengku Mohamad, Tengku Azam Shah; Ismail, Maznah; Baharuldin, Mohamad Taufik Hidayat; Israf Ali, Daud Ahmad; Adilius, M. (Informa Healthcare, 2010)
Alpinia conchigera Griff. (Zingiberaceae), locally known to the Malays as "lengkuas ranting", is native to Peninsular Malaysia. The Malays traditionally used it to treat infection and rashes, and as a health drink. This study evaluated the analgesic and anti-inflammatory activities of the ethanol extract of A. conchigera rhizomes in mice and rats, respectively. The analgesic activity was elucidated using the acetic acid-induced writhing test, hot plate test, and formalin test, while the anti-inflammatory activity was determined using carrageenan-induced paw edema. The extract (30, 100, and 300mg/kg) given intraperitoneally (i.p.) exhibited antinociceptive and anti-inflammatory activities in all tests used. The range of percentage of analgesia obtained for all doses of extract in the writhing test was 5092%, and in the early and late phases of the formalin test was 2562% and 6398%, respectively. In addition, naloxone (5mg/kg) given subcutaneously (s.c.) was found to reverse the extract (300mg/kg)-induced antinociceptive activity in the writhing, hot plate, and formalin tests. Based on the results obtained, it can be concluded that the ethanol extract of A. conchigera rhizomes possessed a peripheral and central antinociceptive activity that was mediated, in part, via the opioid receptor, as well as anti-inflammatory activity.